2014
DOI: 10.1111/idh.12068
|View full text |Cite
|
Sign up to set email alerts
|

Effects of professional oral health care on elderly: randomized trial

Abstract: The short-term professional oral health care can improve oral conditions in the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…Therefore, a set of CPGs was created for each type of restoration comprising (1) patient recall, (2) professional maintenance, and (3) at-home maintenance. The CPGs are presented in Table 3 for tooth-borne restorations [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and Table 4 for implant-borne restorations. [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] For tooth-borne restorations, the professional maintenance and at-home maintenance CPGs were subdivided for removable and fixed restorations.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a set of CPGs was created for each type of restoration comprising (1) patient recall, (2) professional maintenance, and (3) at-home maintenance. The CPGs are presented in Table 3 for tooth-borne restorations [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and Table 4 for implant-borne restorations. [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] For tooth-borne restorations, the professional maintenance and at-home maintenance CPGs were subdivided for removable and fixed restorations.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a set of CPGs was created for each type of restoration comprising (1) patient recall, (2) professional maintenance, and (3) at‐home maintenance. The CPGs are presented in Table for tooth‐borne restorations and Table for implant‐borne restorations . For tooth‐borne restorations, the professional maintenance and at‐home maintenance CPGs were subdivided for removable and fixed restorations.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies (all RCTs) reported on professional interventions (oral hygiene instruction or oral hygiene intervention) that demonstrated improvement of oral health outcomes. Zenthöfer et al and Morino et al independently conducted studies in nursing homes on partially edentulous patients with both natural teeth and partial RDPs and concluded that professional oral health intervention (including professional cleaning of teeth and dentures and manual brushing by hygienists) significantly improved oral health conditions in the elderly. Two additional RCTs by De Visschere et al and van der Putten et al also conducted in nursing home settings on partially edentulous patients showed that implementation of an oral hygiene instruction program was more effective than a nonsupervised program in improved oral health conditions in the elderly.…”
Section: Resultsmentioning
confidence: 99%
“…Each requires careful planning, meticulous coordination of care, and a long‐term partnership with the patient to maintain an enduring result. This includes an appropriate patient recall regimen, professional maintenance, as well as at‐home maintenance . Although the dentist and patient share the mutual goal of esthetic and enduring treatment, the options and relative merits of maintenance protocols to predictably achieve stable results are lacking.…”
mentioning
confidence: 99%
See 1 more Smart Citation